Water surface platform for internet-based environmental monitoring system - Kafli, Nurliyana (2019)
Currently, environmental monitoring plays such an important role in human life. This research work was carried out to monitor the environment of air and water quality that displayed the data through the mobile phone or computer. This is due to several challenges while monitoring the environment such as accessibility to a site and the safety of the workers. This research work consists of several sensors that were attached to the water surface platform (WSP); carbon monoxide sensor, temperature and humidity sensor, pH sensor, and depth sensor that acts as an input. Besides that, a GPS module also attached to the platform to track down the position of the platform in terms of latitude and longitude. Through this input, the WSP also collects the data of the carbon monoxide released to determine the quality of air, while the data on the pH value and the value of temperature and humidity were collected to determine the quality of water based on Class IV- irrigation. This research work also detects the water level for flood warning and sends a warning to the authorities through Short Message Service (SMS). As a result, all the data from the sensors were successfully sent to the ThingSpeak IoT platform to be monitored by the authorities. The graph for each sensor was generated in the ThingSpeak channel to easier the authorities. The SMS of the parameters’ value also sent to the mobile phone. The power load of the WSP is 10.84W with the total time consumed of one hour and 36 seconds by using Li-ion battery. There is a slightly difference in transferring the data to the ThingSpeak channel and sending SMS due to some delays in coding part. Based on the results obtained when the WSP was deployed at FKAAS Lake in UTHM, the lake can be classified as class IV type. The long-term goal of this research is to ensure that the authorities can monitor the changes that happened on the website without the needs to be at the site.